National Security, Social Order and the Quest for Human Dignity in Nigeria: Some Ethical Considerations (Nordic Journal of African Studies, 2001)
This essay examines the ethical factors embedded in the problem of national security in Nigeria. It argues that the foundation of Nigeria's national security needs to be redefined due to the visible failure of the hitherto restrictive military and economic approaches to national survival and development. The essay examines the connection between security issues and moral considerations by analyzing the moral and social values indispensable for the establishment of enduring national security in Nigeria. In short, the essay discusses the critical challenges confronting Nigeria in its quest for the establishment of enduring and genuine national security and sustainable development, both from a historical and conceptual point of view.